Telomere Length in Neonatal Dairy Calves in Relation to Lifetime Parameters - Manon Dewulf; Luc Duchateau; Maya Meesters; Dries S. Martens; Tim S. Nawrot; Mieke Van Eetvelde; Geert Opsomer (Animals)
Telomere length (TL) has gained attention as a biomarker for longevity and productivity in dairy cattle. This study explored the association between neonatal TL in Holstein calves and lifetime parameters (lifespan, milk production, and reproduction). Blood samples were collected from 210 calves (≤10d old) across four dairy farms in Flanders, Belgium. Telomere length was measured using qPCR and analyzed as a continuous variable and across three groups: the 10% shortest, the 10% longest, and the remaining 80%. Survival analyses showed no association between TL and lifespan (p = 0.1) or TL groups (p = 0.8). Similarly, TL showed no significant association with production traits. However, categorical analyses revealed that calves with the longest TL had lower lifetime fat (p = 0.01) and protein yields (p = 0.01) than those with the shortest TL. Reproductive analyses showed cows in the long TL group required fewer inseminations per lactation (p = 0.02) and exhibited longer calving intervals (p = 0.05). These findings suggest that while neonatal TL may not predict productive lifespan, it may provide insight into reproductive efficiency. Future studies should prioritize longitudinal assessments of TL dynamics to better understand their interactions with management practices and application in herd improvement.